The Forgotten Bonds: A Coevolutionary Framework on the Diffusion of Tzu Chi in Four Southeast Asian Countries. (September 2020) - Lee, Chengpang
The literature on the diffusion of new religion is strongly influenced by the voluntaristic paradigm that highlights the agency of individual migrants. This article examines and compares the diffusion process and outcome of Tzu Chi (Buddhist Compassion Relief Tzu Chi Association) in four Southeast Asian countries—Malaysia, Indonesia, Singapore, and the Philippines—to illustrate the complex relationship between migration, diffusion, critical events, and local conditions. Using a comparative research design and original materials, this article proposes a coevolutionary framework inspired by organization studies on the emergence of novelty. This article argues that the different diffusion processes and diffusion outcomes in the four cases are best explained through looking at network genesis mechanisms. This research contributes to the current studies on the diffusion of religion and scholarly interests in the global Tzu Chi movement.